Development Of Ethnoscience-Based E-Modules On Photosynthesis Subject For Elementary School Students - Lestari, Dita Dwi; Yasa , Arnelia Dwi; Kumala , Farida Nur (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Learning carried out by teachers tends to use the lecture method, using minimized image and color media so that it makes students bored, not only that teachers tend to use printed books. This type of research uses development research or R&D. The data collection techniques used are observation and interviews, validation, teacher questionnaires and student responses, the data analysis techniques used include quantitative and qualitative analysis for data collection instruments using test sheets and questionnaire sheets. E-modules are validated to experts, namely material, media and language experts, the data obtained include, among others, material expert validation of 93% with a very feasible category, media expert validation of 97% with a feasible category, and language experts of 84% with a feasible category. To measure the effectiveness of the e-module, a pretest and posttest were conducted, and a T test was conducted which showed that H0 was rejected and H1 was accepted so that there were changes that differentiated before and after treatment, it can be concluded that this media is effective to use. The results of the student questionnaire showed a value of 64% in the practical category. The results of the research conducted show that the Ethnosain-based IPAS e-module is effective as a learning support media, because the e-module can improve students' learning abilities.